2015
DOI: 10.1007/s12016-015-8497-4
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and Systemic Lupus Erythematosus: Unmet Needs

Abstract: Systemic lupus erythematosus (SLE) is a chronic relapsing-remitting autoimmune disease affecting several organs. Although the management of lupus patients has improved in the last years, several aspects still remain challenging. More sensitive and specific biomarkers for an early diagnosis as well as for monitoring disease activity and tissue damage are needed. Genome-wide association and gene mapping studies have supported the genetic background for SLE susceptibility. However, the relatively modest risk asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…While for some epigenetic alterations (particularly histone modifications and miRNAs) epigenetic treatment appears within reach, targeted alteration of DNA methylation appears even more complex [165]. However, epigenetic events cannot easily be dissected into DNA methylation, histone modifications and miRNA expression, since epigenetic events affect one another and epigenetic patterns can be 'translated' [14,16,17].…”
Section: Epigenetic Alterations As Biomarkers For Slementioning
confidence: 99%
See 1 more Smart Citation
“…While for some epigenetic alterations (particularly histone modifications and miRNAs) epigenetic treatment appears within reach, targeted alteration of DNA methylation appears even more complex [165]. However, epigenetic events cannot easily be dissected into DNA methylation, histone modifications and miRNA expression, since epigenetic events affect one another and epigenetic patterns can be 'translated' [14,16,17].…”
Section: Epigenetic Alterations As Biomarkers For Slementioning
confidence: 99%
“…Interactions between DNA methylation and other epigenetic events are briefly discussed. A detailed discussion of involved mechanisms, however, is beyond the scope of this manuscript and reviewed elsewhere [16,17].…”
mentioning
confidence: 99%
“…Currently, our advanced understanding of the genetic mechanism underlying SLE indicated that epigenetic changes, such as disease-associated susceptibility gene regulation, noncoding RNA regulation, and post-transcriptional modifications (Meroni and Penatti, 2016;Mazzone et al, 2019), play important roles in SLE. For example, our previous study demonstrated that abnormally expressed microRNAs and non-coding circular RNAs (circRNAs) are involved in SLE pathogenesis and are potential diagnostic markers (Guo et al, 2018(Guo et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Although differences in several genes were reported, their clinical implications and relevance remain elusive. In fact, in PBC and all other autoimmune diseases, the results of genome‐wide association studies have been disappointing, and recent efforts have been directed to both deep sequencing and consideration of epigenetic events …”
Section: Genetic and Environmental Influences: Xenobiotic Modificatiomentioning
confidence: 99%